The PRODUCT DIVERSITY, PRODUCT QUALITY AND PRODUCT BRAND ON PURCHASING DECISIONS WITH WORD OF MOUTH AS MODERATION: CASE STUDY OF MALLICA GLOW IN JAMBI - Oktaviani, Singki; Yacob, Syahmardi; Lubis, Tona Aurora (Journal of Business Studies and Management Review, 2024)
This research aims to analyze the influence of product diversity, product quality and product brand on purchasing decisions with word of mouth as a moderating variable for Mallica Glow products in Jambi City. This research uses a quantitative method with a Partial Least Square (PLS) approach. Data was collected through a questionnaire distributed to Mallica Glow consumers in Jambi City. The research results show that product diversity, product quality, and product brand have a significant and positive effect on purchasing decisions. However, word of mouth does not have a significant effect on purchasing decisions and does not moderate the influence of product diversity, product quality and product brand on purchasing decisions. Thus, companies are advised to continue to increase product diversity, product quality and product brands to increase consumer purchasing decisions, as well as continue to manage word of mouth effectively even though it is not a significant moderating factor.